Conhecimento, atitude e prática de enfermeiros sobre autocuidado em hanseníase: tecnologia para educação na saúde - Antas, Ester Missias Villaverde (2025)
Introduction: Leprosy is a communicable, disabling disease characterized by a slow and progressive course of illness. In Primary Health Care (PHC), it is essential to utilize technologies that support health education and enhance self-care guidelines for nurses, aiming to prevent disabilities and deformities in individuals with leprosy. Objective: To develop a technology for the elaboration of a Situational Strategic Plan for Health Education for PHC nurses, with an emphasis on self-care guidelines for the face, hands, and feet of people with leprosy. Method: Research conducted in João Pessoa from September 2022 to March 2025, developed in three stages: a methodological study to construct and validate the instrument Knowledge, Attitude, and Practice regarding self-care in leprosy; an evaluative study to characterize the knowledge, attitude, and practice of 69 PHC nurses regarding self-care guidelines for the face, hands, and feet of people with leprosy; and situational strategic planning for the PHC context. Descriptive statistical techniques were applied, along with analysis of the Content Validity Index (CVI) and consistency, as measured by Cronbach's alpha (α), with a 95% confidence interval. The research was approved by the Research Ethics Committee, with opinion no. 5,655,957. Results: The instrument presented a satisfactory Overall CVI for the criteria of Clarity (CVI 0.96) and Relevance (CVI 0.98), and substantial internal consistency (α = 0.67). The evaluative study showed inadequate knowledge (except for the feet), attitude, and practice regarding self-care guidelines for the face and limbs of people with leprosy. In the Situational Strategic Plan, an Action Plan was developed for the future implementation of Health Education for PHC nurses. Conclusion: The validated instrument presented satisfactory content and demonstrated potential for use in future studies; the characterization of nurses' knowledge, attitude, and practice regarding self-care guidelines for the face, hands, and feet of people with leprosy was fundamental for the elaboration of an Action Plan directed at the real learning needs of the group, anchored in a theoretical framework that considers prior knowledge.